Study of Effect of Amlodipine on Blood Sugar Level - Sandozi, Tasneem (Asian Journal of Medical Sciences, 2010)
Objective: To study the effect of AMLODIPINE on blood sugar levels in hypertensive patients. Method: It is a prospective study in which patients were selected from Princess Esra hospital, Hyderabad. Results: This study was done on 20 mild to moderate newly detected hypertensive patients. Statistical analysis shows a highly significant rise in blood sugar level with ‘P' value < 0.001 after 2 and 4 weeks of using 2.5 to 5 mgm (once daily) amlodipine. Conclusion: As calcium channels are involved in the release of insulin from the β cells of pancreas, calcium channel blockers like amlodipine may cause hyperglycemia when used in hypertensive patients. Further studies are required in this field on a larger number of patients. Keywords: Amlodipine; Calcium channel blockers; Diabetes Mellitus; Hypertension DOI: 10.3126/ajms.v1i1.2777 Asian Journal of Medical Sciences Vol.1(1) 2010 p.4-5